Study on dynamic sand collapse mechanism of weakly consolidated rock strata in thick bedrock stope in western China - Liu Zhaoxing; Dong Shuning; Guo Xiaoming; Li Xiaolong; Liu Yingfeng; Guo Kang (Scientific Reports)
Abstract The superimposed disaster of water and sand collapse and strong ore pressure appearance in the two coal bases of Huanglong and Ningdong mining areas in western China is a kind of dynamic sand collapse disaster of weakly consolidated rock strata in the roof of thick bedrock mining. This type of disaster is a new type of stope roof disaster, which is different from the previous non-dynamic water and sand collapse disasters in shallow buried and near loose layer stope in terms of appearance, material source and power source. As this type of disaster is sudden, destructive and powerful, it poses a serious threat to the safety of production, so how to effectively prevent and control the recurrence of disasters has become a difficult problem to be solved in many mining areas. By means of theoretical analysis, numerical calculation and laboratory tests, this paper analyzes and studies the overlying rock failure characteristics of stope, hydraulic gradient conditions of aquifer, physical and mechanical characteristics of weakly consolidated formation and its mineral composi-tion from the perspective of the source and power source of disaster formation, etc., and reveals the internal relationship between mine pressure of accident stope and the disaster caused by weakly consolidated formation. The typical overburden formation structure characteristics of dynamic sand collapse disaster in weakly consolidated formation are put forward, and the necessary conditions for disaster occurrence are the mudstone roof strata of weakly consolidated Zhiluo Formation containing a large number of hydrophobic minerals (provenance) and the slide and instability of composite key strata (power source). The research results will provide theoretical support for the construction of prevention and control technology system for the disaster caused by water and sand collapse of stope roof and the occurrence of strong mine pressure, and ensure the large-scale safety development of coal fields in western China.